Uji Aktivitas Antibakteri dan Skrining Fitokimia Ekstrak Metanol Buah Hitam (H. monticola.) Asal Kabupaten Teluk Wondama - Elsarina Siahaan; Bimo B. Santoso; Evelina Somar; Maria Massora (FMIPA Universitas Papua, 2021)
This study aimed to test the antibacterial activity and identify the secondary metabolite contect of the methanol extract Black Fruit (H. monticola). The black fruit extract was obtained through the maceration extraction method using methanol as a solvent. The result of phytocemical screening showed that the methanol extract of black fruit (H. monticola) contained high levels of tannins and saponins. Antibacterial activity test was carried out using the wall method with postive control of chloromphenicol and negative control with methanol. The result of antibacterial activity test against E.Coli bacteria showed strong activity with an inhibition zone diameter of 11 mm and B. Subtilis bacteria showed moderate activity with an inhibition zone with a diameter of 8 mm